Exploring the immunomodulatory effects of human mesenchymal stem cells on monocyte functions - Maqbool, Maryam (2016)
Monocytes are essential phagocytic cells of the innate immune system. They maintain normal tissue homeostasis but they are also implicated in various chronic inflammatory diseases. It has been shown that mesenchymal stem cells deliver immunosuppressive activities on adaptive and innate immune cells. Therefore this study has explored the less understood immunomodulatory effects of mesenchymal stem cells on primary and secondary monocyte (cell lines THP-1 and U937) functions. Primary and secondary monocytes were co-cultured with human umbilical cordderived MSCs at appropriate culture conditions to assess the monocyte’s vital functions such as differentiation, phagocytosis, antigen presentation capability, cellular proliferation, cell cycle and apoptosis. Based on immunophenotyping and morphological analysis, mesenchymal stem cells significantly inhibited monocyte differentiation into dendritic cells and macrophages. Evidenced by lack of expression of maturation markers, co-stimulatory molecules and MHC class II molecule. Additionally, the gene expression of selected important genes (TNFRSF11A, TGF-A, FGFR1 and C3) were analysed using quantitative real time PCR (qPCR) to verify mesenchymal stem cells mediated inhibition on monocyte’s differentiation at mRNA level. Mesenchymal stem cells significantly inhibited the expression of TNFRSF11A and FGFR1 in relevant cells. In the presence of mesenchymal stem cells, monocytes, dendritic cells and macrophage exhibited declined phagocytosis followed by inability to stimulate T cell proliferation via PHA antigen presentation. Mesenchymal stem cells suppressed monocyte proliferation in a dose dependant manner. The antiproliferative effect of mesenchymal stem cells was mediated by cell cycle arrest whereby they were able to arrest monocytes in G0/G1 phase preventing progression into S and G2/M phases of cell cycle. Cell cycle arrest could potentially lead to cell apoptosis. However, mesenchymal stem cells significantly enhanced the monocytes survival and inhibited their apoptosis. Mesenchymal stem cell-mediated immunosuppression was not confined to primary monocytes it was also extended towards secondary monocytes. In the presence of mesenchymal stem cells, the differentiation, proliferation, phagocytosis and apoptosis of secondary monocytes were significantly abrogated. Over all, this study confers that mesenchymal stem cells exerted immunosuppressive effects on primary and secondary monocyte functions. Consequently this thesis makes a compelling case for the use of mesenchymal stem cells in treating and managing the unwanted immune responses such as in graft versus host disease and other forms of chronic inflammatory diseases. Moving forward it is imperative to further understand the mechanisms involved in MSC mediated immunosuppression.